Standarisasi Mutu Musyrif Dalam Menjamin Kualitas Pendidikan di Ma’had Aly Nurul Jadid - Hikmatul Hidayah; Mawadatur Rohmah (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2024)
This research is a qualitative research that aims to find out and evaluate how much the quality standards of musyrif and musyrifah services and the quality of musyrif musyrifah in the academic process in Ma'had Aly Nurul Jadid. Musyrif musyrifah here is a manager and mobilizer who accompanies, helps, motivates, conditions and directs students in Ma'had Aly Nurul Jadid. This musyrifah musyrifah becomes a supervisor and guide in the learning process both in academic programs and takhassus. The results showed that the standardization of the quality of musyrif musyrifah can be concluded, namely with the musyrif musyrifah service to the program that runs in mahad aly where musyrif musyrifah becomes a parent, supervisor, guide as well as a place to find insight into the book of turats. The second standardization can be expressed by the quality of the musyrif musyrifah itself both seen from the academic quality that has been carried out before becoming a graduate of Mahad Aly, it can also be known from the service that has been carried out. So in this case, musyrif musyrifah studies and applies his knowledge with scientific charity and amaliyah science.